The red pyramid : the graphic novel - Collar, Orpheus; Riordan, Rick.; Fletcher, Jared K. (New York : Disney/Hyperion Books, 2012)
Brilliant Egyptologist Dr. Julius Kane accidentally unleashes the Egyptian god Set, who banishes the doctor to oblivion and forces his two children to embark on a dangerous journey, bringing them closer to the truth about their family and its links to a secret order that has existed since the time of the pharoahs.
"Adapted from the novel The Kane Chronicles, Book One: The Red Pyramid"--Colophon.
Keywords: Riordan, Rick. -- Adaptations; Seth -- (Egyptian deity) -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Mythology, Egyptian -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Secrecy -- Juvenile fiction; Egypt -- Juvenile fiction; Action and adventure comics; Graphic novels